Loss of bile salt export pump aggravates lipopolysaccharide‐induced liver injury in mice due to impaired hepatic endotoxin clearance. Issue 5 (19th January 2022) - Remetic, Jelena; Ghallab, Ahmed; Hobloss, Zaynab; Brackhagen, Lisa; Hassan, Reham; Myllys, Maiju; Radun, Richard; Mlitz, Veronika; Zhu, Ci; Baumgartner, Maximilian; Schrottmaier, Waltraud C.; Mussbacher, Marion; et al.
Abstract: Background and Aims: Lipopolysaccharide (LPS) clearance is delayed in cholestatic liver diseases. While compromised clearance by Kupffer cells (KCs) is involved, the role of LPS uptake into hepatocytes and canalicular excretion remains unclear. Approach and Results: Wild‐type (WT) and bile salt export pump (Bsep) knockout (KO) mice were challenged i.p. with LPS. Liver injury was assessed by serum biochemistry, histology, molecular inflammation markers, and immune cell infiltration. LPS concentrations were determined in liver tissue and bile. Subcellular kinetics of fluorescently labeled LPS was visualized by intravital two‐photon microscopy, and the findings in Bsep KO mice were compared to common bile duct–ligated (BDL) and multidrug resistance protein 2 (Mdr2) KO mice. Changes in gut microbiota composition were evaluated by 16S ribosomal RNA gene amplicon sequencing analysis. Bsep KO mice developed more pronounced LPS‐induced liver injury and inflammatory signaling, with subsequently enhanced production of proinflammatory cytokines and aggravated hepatic immune cell infiltration. After LPS administration, its concentrations were higher in liver but lower in bile of Bsep KO compared to WT mice. Intravital imaging of LPS showed a delayed clearance from sinusoidal blood with a basolateral uptake block into hepatocytes and reduced canalicular secretion. Moreover, LPS uptake into KCs was reduced. Similar findings with respect to hepatic LPS clearance were obtained in BDL and Mdr2 KO mice. Pretreatment with the microtubule inhibitor colchicine inhibited biliary excretion of LPS in WT mice, indicating that LPS clearance is microtubule‐dependent. Microbiota analysis showed no change of the gut microbiome between WT and Bsep KO mice at baseline but major changes upon LPS challenge in WT mice. Conclusions: Absence of Bsep and cholestasis in general impair LPS clearance by a basolateral uptake block into hepatocytes and consequently less secretion into canaliculi. Impaired LPS removal aggravates hepatic inflammation in cholestasis. Abstract : image